2014
DOI: 10.1590/1981-5344/1884
|View full text |Cite
|
Sign up to set email alerts
|

Flexibilidad y teletrabajo: un estudio bibliométrico sobre la producción científica

Abstract: Este artículo tiene como objetivo estudiar y analizar un conjunto de autores, periódicos y palabras clave que se relacionan a flexibilidad y teletrabajo. Para ello, se aplicó la metodología de revisión sistemática de la literatura en cuatro bases de datos científicas, proceso que identificó 80 estudios sobre el tema buscado. Los resultados muestran que las investigaciones más relevantes, de acuerdo con el número de citaciones, son de países anglosajones (EE.UU., Canadá y Reino Unido, respectivamente), que hay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Lastly, it is important to emphasize that publications and research on telework in Latin America are scarce. A systematic review of literature related to telework and work flexibility in four scientific databases carried out by Da Silva (2014) found that almost all publications come from Anglo-Saxon countries. However, this does not mean that the issue has gone unnoticed.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, it is important to emphasize that publications and research on telework in Latin America are scarce. A systematic review of literature related to telework and work flexibility in four scientific databases carried out by Da Silva (2014) found that almost all publications come from Anglo-Saxon countries. However, this does not mean that the issue has gone unnoticed.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, the work-life balance challenge has become a central issue in this pandemic, both in relation to caring for dependents and, in a broader sense, to work-life balance and work-life separation. In the case of teleworking, although the literature has outlined its advantages for work-life balance [28], the difficulties created by the permeability between work and family life [34], family interference [31] and family disputes caused by poor delimitation of spaces [32,33] were salient in an emergency context where workers had to exercise care-giving tasks without the support available in a normal situation (Study 1). In fact, results of Study 2 also showed that workers with care responsibilities expressed greater difficulties in balancing work with family and family with work.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, people who telework regularly tend to experience low work-family conflict [31,32]. Even so, several studies point out the difficulties created by the lack of separation or permeability between work and family life, reporting family disputes caused by poor boundaries (referring to both work-family and family-work conflict) [32][33][34]. The difficulties in carrying out work because of family interference are also highlighted, in the particular context of family-work conflict.…”
Section: Work-life Balance In Times Of Pandemicmentioning
confidence: 99%
“…Research on WF has focused on flexibility in work location, work schedules or forms of communication (Demerouti et al, 2014;Ray and Pana-Cryan, 2021), and even wage and functional flexibility (ILO, 2022). This flexibility can be achieved by mutual agreements between the worker and the company based on trust and years of work, but in some cases, it is motivated by the design of the workplace, such as the consideration of telework (Da Silva, 2014;Karkuzashvili, 2021), as employees can change the location and reconcile their family life activities with work.…”
Section: Work Flexibility (Wf) and Job Happiness (Jh)mentioning
confidence: 99%